2018
DOI: 10.3389/fphys.2018.00933
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Naoxueshu Promotes Improvement of Hematoma Absorption and Neurological Function in Acute Intracerebral Hemorrhage Patients

Abstract: Aims: To evaluate the clinical efficacy of Naoxueshu oral liquid in the treatment of intracerebral hemorrhage (ICH) patients.Methods: In our study, December 2008 to August 2010, 88 patients with intracerebral hemorrhage were enrolled and 87 patients with complete information of whom 44 patients received Naoxueshu oral liquid plus regular treatment (Naoxueshu group), 43 patients received regular treatment (control group) only. Naoxueshu oral liquid 10 ml was taken in the Naoxueshu group, with 3 times a day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Previous study found anti‐inflammatory effects of Naoxueshu because the level of white blood cell (WBC) count was decreased more significantly in Naoxueshu treatment patients (Song et al., 2018). However, in this study, change of WBC count was not so significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study found anti‐inflammatory effects of Naoxueshu because the level of white blood cell (WBC) count was decreased more significantly in Naoxueshu treatment patients (Song et al., 2018). However, in this study, change of WBC count was not so significant.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma volume (ml) = π /6 × length (cm) × width (cm) × high (cm) (Song et al., 2018), and it was determined by CT scanning (Siemens 64‐slice CT machine, section thickness, 5 mm; gap, 5 mm; pitch, 1; tube current, 304mA; and voltage, 120 kV).…”
Section: Methodsmentioning
confidence: 99%
“…The NIHSS rater was an independent investigator who was blinded of our study in each site. Hematoma volume (ml) = π/6 × length (cm) × width (cm) × high (cm) [ 14 ], and it was determined by CT scanning (Siemens 64-slice CT machine, section thickness, 5 mm; gap, 5 mm; pitch, 1; tube current, 304 mA; and voltage, 120 kV).…”
Section: Methodsmentioning
confidence: 99%
“…In the eld of traditional Chinese medicine (TCM), more and more attention was xed on the therapy of stroke, especially hemorrhagic stroke [8]. Song et al found that Naoxueshu oral liquid can signi cantly reduce the in ammation and edema of ICH [9]. And Li et al reported that tsRNAs may be the potential targets for Buyang Huanwu Decoction against ICH [10].…”
Section: Introductionmentioning
confidence: 99%